Preparation and utilization of ubi flour - Riguera, Concepcion C. ([Quezon City], 1959)
The aim of this study is to observe the effect of drying and powdering on the color and flavor of the ubi when made into flour for use in various native delicacies. Fresh ubi tubers were steamed, passed through a meat grinder, dried, and milled. The cooking qualities of the flour were tested by making it into various native delicacies. The products were evaluated subjectively by five judges for color, flavor, texture and aroma. Similar products made from fresh ubi were taken as standards of reference. The properties of ubi flavor of greatest culinary importance are: (1) color, (2) flavor, and (3) texture.
Literature cited: l. 30.
Thesis (B.S. Food Tech.)--University of the Philippines.
Keywords: Yam flour